Acute Mono-Arthritis Activates the Neurohypophysial System and Hypothalamo-Pituitary Adrenal Axis in Rats - Nishimura, Haruki; Kawasaki, Makoto; Matsuura, Takanori; Suzuki, Hitoshi; Motojima, Yasuhito; Baba, Kazuhiko; Ohnishi, Hideo; Yamanaka, Yoshiaki; Fujitani, Teruaki; Yoshimura, Mitsuhiro; Maruyama, Takashi; Ueno, Hiromichi; et al. (Frontiers in Endocrinology, 2020)
Various types of acute/chronic nociceptive stimuli cause neuroendocrine responses such as activation of the hypothalamo-neurohypophysial (oxytocin [OXT] and arginine vasopressin [AVP]) system and hypothalamo-pituitary adrenal (HPA) axis. Chronic multiple-arthritis activates the OXT/AVP system, but the effects of acute mono-arthritis on the OXT/AVP system in the same animals has not been simultaneously evaluated. Further, AVP, not corticotropin-releasing hormone (CRH), predominantly activates the HPA axis in chronic multiple-arthritis, but the participation of AVP in HPA axis activation in acute mono-arthritis remains unknown. Therefore, we aimed to simultaneously evaluate the effects of acute mono-arthritis on the activity of the OXT/AVP system and the HPA axis. In the present study, we used an acute mono-arthritic model induced by intra-articular injection of carrageenan in a single knee joint of adult male Wistar rats. Acute mono-arthritis was confirmed by a significant increase in knee diameter in the carrageenan-injected knee and a significant decrease in the mechanical nociceptive threshold in the ipsilateral hind paw. Immunohistochemical analysis revealed that the number of Fos-immunoreactive (ir) cells in the ipsilateral lamina I-II of the dorsal horn was significantly increased, and the percentage of OXT-ir and AVP-ir neurons expressing Fos-ir in both sides of the supraoptic (SON) and paraventricular nuclei (PVN) was increased in acute mono-arthritic rats. In situ hybridization histochemistry revealed that levels of OXT mRNA and AVP hnRNA in the SON and PVN, corticotropin-releasing hormone mRNA in the PVN, and proopiomelanocortin mRNA in the anterior pituitary were also significantly increased in acute mono-arthritic rats. Further, plasma OXT, AVP, and corticosterone levels were significantly increased in acute mono-arthritic rats. These results suggest that acute mono-arthritis activates ipsilateral nociceptive afferent pathways at the spinal level and causes simultaneous and integrative activation of the OXT/AVP system. In addition, the HPA axis is activated by both AVP and CRH in acute mono-arthritis with a distinct pattern compared to that in chronic multiple-arthritis.